Foraminiferal Ecology and Role in Nitrogen Benthic Cycle in the Hypoxic Southeastern Bering Sea - Langlet, Dewi; Bouchet, Vincent M. P.; Riso, Riccardo; Matsui, Yohei; Suga, Hisami; Fujiwara, Yoshihiro; Nomaki, Hidetaka (Frontiers in Marine Science, 2020)
Southeastern Bering Sea is one of the highest surface productivity area in the open ocean due to strong upwelling along the Bering canyon. However, the benthic geochemistry and organisms living in the area have been largely overlooked. In August 2017, surface sediment was sampled from four stations along a transect at depths between 1536 and 103 meters in the Bering canyon with JAMSTEC R/V Mirai. Bottom-water hypoxia was recorded in the two deepest stations (1536 and 536 m). At these stations, the oxygen penetrated down to 5 mm in the sediment due to siltier and much organic-rich sediments in the deeper stations while oxygen penetration was about 20 mm at stations 103 and 197 meters deep with coarse-grained sediment stations. Foraminiferal number of species and abundances were higher in the Unimak pass depression station E2 (197 m). Abundance did not change significantly between stations, suggesting that foraminiferal densities are not affected by the hypoxic conditions but are rather controlled by organic matter and nutrients availability. At the upper bathyal and middle bathyal stations, living foraminiferal communities were in general dominated by Uvigerina peregrina, Nonionella pulchella, Elphidium batialis, Globobulimina pacifica, Reophax spp., and Bolivina spathulata while the shallower stations exhibited large densities of Uvigerina peregrina, Cibicidoides wuellerstorfi, Recurvoidella bradyi, Globocassidulina subglobosa, and Portatrochammina pacifica. More than 50% of the individuals have a potential to accumulate nitrate in their cell (from 3 to 648 mmol/L; which is from 100 to 4000 times larger than the highest concentration measured in pore water). Onboard denitrification measurements confirmed that B. spathulata, N. pulchella and G. pacifica could reduce nitrate through denitrification and foraminiferal denitrification could contribute over 6% to benthic nitrate reduction at the southeast Bering Sea. Although the foraminiferal contributions were smaller than those measured at other hypoxic areas, our study quantitatively revealed the significance of eukaryotic microbes on benthic nitrogen cycles at this area.